Atividades para o aprendizado de acústica - Rodrigues, Ernani Vassoler (2016)
In this work we report on the design, application and evaluation of an educational product to a senior high school students group (N=28) from a private institution at Vitória city, Espirito Santo state, Brazil. We also report on the students’ gain in learning the proposed concepts and the evaluation of the educational product’s viability. The activities include basic concepts on acoustics and usage of smartphones, Arduino as well as rudimentary musical instrument and audio speaker crafting. This work is under DiSessa’s and colleagues’ ideas for Conceptual Change theory. DiSessa argues that concepts change by the revision, adequacy or refutation of knowledge fragments in the conceptual system. The coordination of these fragments drives to an inferential network construct that allows one to predict or explain physical phenomena. The evaluation tools were: student’s ability change – via Rasch analysis – and self-ecacy sense in multiple choice tests; mind map; word network association; and focal group interviewing. The results showed traces of concept evolution (in a sense of change), students’ ability gain, increase of self-ecacy sense, acquisition of scientific language terms and change in the topology and edge’s frequency based on scientific reasoning for the word network. The students’ statements pointed out to activities as a viable educational tool, highlighting aspects such as curiosity and interest within the activities despite some diculty reported.